PENGARUH KARAKTERISTIK AUDIT DAN UKURAN PERUSAHAAN TERHADAP EARNINGS MANAGEMENT: STUDI EMPIRIS PADA PERUSAHAAN INDEKS LQ45 PERIODE 2021-2024 - Ananda Kurnia Mulyatno; Tarmizi Achmad (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of audit characteristics and company size on earnings management. The independent variables in this study are audit characteristics, proxied by the size of the public accounting firm (KAP) and industry specialization, while company size is measured by the natural logarithm of total assets. Earnings management, which is the dependent variable, is measured by calculating discretionary accruals. The population in this study consists of companies with consistent LQ45 indexing from 2021 to 2024. Using purposive sampling, 96 samples were taken from LQ45 index companies that published annual financial reports on the IDX website. This study uses multiple linear regression analysis to test the effects of KAP size, industry specialization, and company size on earnings management. The results of this study indicate that industry specialization has a significant negative effect on earnings management, while KAP size and company size have no significant effect on earnings management.